Taalseksisme in die leksikon : met spesifieke verwysing na Afrikaans - Vermaak, Rachelle (2015)
M.A. (Afrikaans) === The women's liberation movement, which had its origins in the seventies, produced a number of intellectuals who have been actively campaigning for the eradication of sexism in especially the American society ever since. In terms of this movement, language is deemed to provide the very paradigm within which gender inequality is set to flourish unchecked. One of the principal aims of the movement is, therefore, to eliminate all grammatical forms in terms of which women, trapped in a traditionally male-dominated world, are being ignored, slighted, degraded and stereotyped. Soon, several publishers started introducing and organising women's study series and workshops on sexism at conferences on language and sociology. In the wake of that, a great number of publications, in which language inequalities are scientifically described, have appeared already. In addition, many articles and books were published in which guide-lines were laid down for the avoidance of sexist lexical items in the English language, which has since gained the unfortunate distinction of being labelled the most sexist language. The emphasis in the present study will, however, not fall on the ideology underlying the women's liberation movement, but on the many publications on language sexisms that had been prompted by it. Language planning and change naturally play a crucial part in all publicatlons on language sexisms. The general sociolinguistic supposition about language change is that it is prompted by change in the social structure of a society. The advocates of the development of a non-sexist language, however, appeal to the Whorf hypothesis, in terms of which the language structure of a society is deemed to reflect and facilitate its world view. According to the champions of the said hypothesis, however, the reverse of this argument should also hold good, namely that a change in the language structure of a society should bring about an inevitable change in its world view. On the strength of the latter hypothesis, alternatives are suggested for all sexist lexical items, so that v the new-found non-sexist language could help society to create a non-sexist social structure. A definition of the term language sexism has been formulated in the present study, based on the conclusions reached in research articles. The conclusion drawn is that the term sexism could only be applied in respect of language usage relating to women. Although feminists have even coined such phrases as male chauvinist pig, the literature that was taken into study (with the possible exception of that generated by Hauptfleisch, 1989), made no mention whatsoever of the possibility that male terms' could also be considered sexist. Current research projects and existing publications on language sexisms are mainly in English. With the exception of Liebenberg (1976), the few existing research studies in Afrikaans deal with specific topics, such as sexisms in translation practice or teaching material. In the present study, however, the researcher has endeavoured to describe the specific nature of those sexisms found in the Afrikaans lexicon.